Dual‐Stimuli‐Responsive Gut Microbiota‐Targeting Berberine‐CS/PT‐NPs Improved Metabolic Status in Obese Hamsters - Guo, Hui‐Hui; Ma, Chen; Zheng, Wen‐Sheng; Luo, Yang; Li, Cong; Li, Xiao‐Lin; Ma, Xiao‐Lei; Feng, Chen‐Lin; Zhang, Ting‐Ting; Han, Yan‐Xing; Luo, Zhi‐Gang; Zhan, Yun; et al. (Advanced functional materials, 2019)
Gut dysbiosis has been found to be involved in the pathogenesis of energy metabolic disorders and might be a new strategy for these ailments. Berberine (BBR), a botanical medicine, shows therapeutic efficacy in patients with metabolic diseases. Numerous reports have shown BBR's modulating effect on gut microbiota, opening a new avenue to understand BBR's mechanism. In this study, a colon‐specific delivery system, BBR‐CS/PT‐NP, is investigated by the assembly of pH/gut microflora dual stimuli‐responsive nanoparticles for enhancing the interaction between BBR and gut microbiota. After oral administration, the delivering system remains stable in the stomach and small intestine, followed by a burst release of BBR after reaching the colon segment rich in intestinal bacteria. The enzymes produced by bacteria degrade the nanoparticle, causing direct exposure of BBR to gut microbiota. In the high fat diet‐induced obese hamsters, BBR‐CS/PT‐NP intervention inhibits weight‐gain and fat deposition, decreases plasma lipids and glucose levels, improves inflammation condition and insulin resistance, alleviates hepatic steatosis, at a level significantly higher than the pure BBR does. The mechanisms might be attributable to the enhanced interaction between BBR and the gut flora. The results provide a novel proof‐of‐concept for drug delivery targeting gut microbiota to ameliorate metabolic disorders. Gut dysbiosis is involved in the pathogenesis of energy metabolic disorders and represents a new strategy for treating these ailments. In this study, a pH/gut microflora dual stimuli‐responsive system, berberine (BBR)‐CS/PT‐NP with colon‐homing and microbiota‐targeting characteristics, is investigated to enhance the interaction between BBR and the gut microbiota. It provides a novel proof‐of‐concept for drug delivery targeting gut microbiota to ameliorate metabolic diseases.